2008
DOI: 10.1177/0961203308092805
|View full text |Cite
|
Sign up to set email alerts
|

Some antiphospholipid antibodies bind to hemostasis and fibrinolysis proteases and promote thrombosis

Abstract: It is generally accepted that the major autoantigen for antiphospholipid antibodies (aPL) is beta(2)glycoprotein I (beta(2)GPI). Interestingly, some aPL bind to beta(2)GPI and the homologous enzymatic domains of several proteases involved in hemostasis and fibrinolysis, and correspondingly hinder anticoagulant regulation and resolution of clots. These findings are consistent with several early findings of aPL and provide a new perspective about some aPL in terms of their binding specificities and related funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Many studies have shown that complement activation may play an important role in thrombotic events. aPL may activate the complement pathway, generating split products that lead to fetal loss and thrombosis [ 31 , 50 , 51 ]. Pierangeli and colleagues [ 52 ] demonstrated that C3- and C5-deficient mice were resistant to aPL-induced thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that complement activation may play an important role in thrombotic events. aPL may activate the complement pathway, generating split products that lead to fetal loss and thrombosis [ 31 , 50 , 51 ]. Pierangeli and colleagues [ 52 ] demonstrated that C3- and C5-deficient mice were resistant to aPL-induced thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, aPL may bind to A2 and inhibit A2-dependent plasmin generation [ 30 ]. Therefore, aPL may promote various thrombotic events by interacting with these hemostatic and fibrinolytic proteases [ 31 ]. It is of interest to investigate whether some protease-reactive aPL are present in LN patients with GMT.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to antiphospholipid syndrome (APS), aPL antibodies of different isotypes have been found in other immune‐mediated diseases such as systemic lupus erythematosus (SLE), Behçet disease and Takayasu arteritis 11–14 . Importantly, aPL antibodies are heterogeneous, recognizing a variety of antigens including various phospholipids such as cardiolipin, phospholipid‐binding proteins and protein–phospholipid complexes 15–18 . Of these proteins, β2‐glycoprotein I (β2GPI) is now recognized either as the major antigenic target or as the cofactor for aPL antibodies 19 …”
mentioning
confidence: 99%
“…Nevertheless, a rising number of other phospholipid-binding proteins with central functions in the regulation of blood coagulation and fibrinolysis are also targeted by APS-related autoantibodies [29,31]. Ttissue type plasminogen activator, plasminogen, annexin A2 (AnnA2), annexin A5, tissue factor pathway inhibitor (TFPI), protein C, protein S, endothelial protein C receptor, and thrombin, were reported in more than a few papers [32][33][34][35][36][37][38][39][40][41]. More limited data propose other potential antigenic targets, including factor XII, factor XI, factor IX, factor VII/activated factor VII, prekallikrein, high and low molecular weight kininogens, vascular heparan sulfate proteoglycan, complement component C4, complement factor H, CD36, protein Z, activated protein C, plasmin, plasminogen activator inhibitor-1 and heparin-platelet factor 4 [42][43][44][45][46][47][48][49][50].…”
Section: Key Issues About Antigen Specificity Of Aplmentioning
confidence: 99%